2004
DOI: 10.1086/421772
|View full text |Cite
|
Sign up to set email alerts
|

The First IBIS/ISGRI Soft Gamma-Ray Galactic Plane Survey Catalog

Abstract: We report the first high-energy survey catalog obtained with the IBIS gamma-ray imager on board INTEGRAL. The analysis has been performed on the first-year Core Program ISGRI data comprising both Galactic Plane Scan and Galactic Centre Deep Exposure pointings for a total exposure time exceeding 5 Ms. This initial survey has revealed the presence of ∼120 sources detected with the unprecedented sensitivity of ∼1 mcrab in the energy range 20-100 keV. Each source is located to an accuracy between 1Ј and 3Ј, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 14 publications
5
172
1
Order By: Relevance
“…Moreover large fractions of sources have significant (SNR ≥ 7) detections in the 2-5.5, 2-19 and 8-19 keV bands (219, 197 and 133 sources respectively), which have slightly lower percentages (71%, 70% and 64% respectively) of counterparts in the RASS. On the other hand the correlation with the harder INTEGRAL/IBIS Soft γ-ray catalogues (Bird et al 2004(Bird et al , 2006(Bird et al and 2007 give increasing percentages proportionally to the increasing INTEGRAL total exposure and sky coverage (29% with the first, 40% with the second and 53% with the most recent one, using the same 3 radius). If we consider a sample of harder WFC sources (35%), detected (SNR ≥ 10) in the 11-26 keV band, 78% resulted to have a counterpart in the last IBIS catalogue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover large fractions of sources have significant (SNR ≥ 7) detections in the 2-5.5, 2-19 and 8-19 keV bands (219, 197 and 133 sources respectively), which have slightly lower percentages (71%, 70% and 64% respectively) of counterparts in the RASS. On the other hand the correlation with the harder INTEGRAL/IBIS Soft γ-ray catalogues (Bird et al 2004(Bird et al , 2006(Bird et al and 2007 give increasing percentages proportionally to the increasing INTEGRAL total exposure and sky coverage (29% with the first, 40% with the second and 53% with the most recent one, using the same 3 radius). If we consider a sample of harder WFC sources (35%), detected (SNR ≥ 10) in the 11-26 keV band, 78% resulted to have a counterpart in the last IBIS catalogue.…”
Section: Discussionmentioning
confidence: 98%
“…It contains more information on variability over long time scale in the hard X-ray band than for example the ROSAT all-sky survey catalogues, the ASCA 0.7-10 keV (Sugizaki et al 2001) and the first three INTEGRAL-IBIS low galactic latitude surveys (Bird et al 2004;Bird et al 2006;Revnivtsev et al 2004) and the high galactic latitude survey of the Swift-BAT (Markwardt et al 2005), and comparable with the last INTEGRAL-IBIS survey (Bird et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present a multiwavelength study of the fields containing the unidentified INTEGRAL sources IGR J18027−1455 and IGR J21247+5058 (Walter et al 2004), as earlier done in Combi et al (2004) and in Ribó et al (2004) but using here the new positions and information reported in Bird et al (2004). Based on the properties of the sources found at other frequencies inside the error circles in position of the IGR sources, we suggest possible origins for both high-energy sources.…”
Section: Introductionmentioning
confidence: 60%
“…This source was detected with a significance of 6.5σ in the energy range from 20 to 100 keV during only 70 ksec of observations conducted within the same INTEGRAL/IBIS survey of the Galactic plane (Bird et al 2004). The obtained fluxes compared to the Crab are F (20−40 keV) =5.4±0.7 mCrab and F (40−100 keV) =9.3±1.4 mCrab.…”
Section: The Igr J21247+5058 Fieldmentioning
confidence: 97%
See 1 more Smart Citation